2005
DOI: 10.1103/physrevb.72.012507
|View full text |Cite
|
Sign up to set email alerts
|

Voltage noise and surface current fluctuations in the superconducting surface sheath

Abstract: We report the first measurements of the voltage noise in the surface superconductivity state of a type-II superconductor. We present strong evidences that surface vortices generates surface current fluctuations whose magnitude can be modified by the pinning ability of the surface. Simple twostage mechanism governed by current conservation appears to describe the data. We conclude that large voltage fluctuations induced by surface vortices exist while the bulk is metallic. Furthermore, this experiment shows tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…This confirms previous auto and cross correlation experiments of both flux and voltage noises [4], and explains the insensivity of the low frequency noise to bulk perturbations [5], in Pb-In alloys. In these experiments, two parameters, the normalized spectrum of the fluctuator and its correlation length, are experimentally justified but are not explained [3,4]. If the fluctuator is of superficial origin, it should be possible to induce notable changes in the noise characteristics after some surface treatments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This confirms previous auto and cross correlation experiments of both flux and voltage noises [4], and explains the insensivity of the low frequency noise to bulk perturbations [5], in Pb-In alloys. In these experiments, two parameters, the normalized spectrum of the fluctuator and its correlation length, are experimentally justified but are not explained [3,4]. If the fluctuator is of superficial origin, it should be possible to induce notable changes in the noise characteristics after some surface treatments.…”
mentioning
confidence: 99%
“…To the extent that the fluctuators are independent and that the system is large enough, the correlation length can be calculated from the noise power via an usual statistical averaging (the central limit theorem) [2]. Recently, it was shown that no difference can be observed between the flux-flow noise in the mixed state and in the surface superconducting state of a Niobium slab [3]. In other words, the same fluctuator is present with or without a bulk vortex lattice, showing clearly its superficial origin.…”
mentioning
confidence: 99%
“…In the present geometry, B is perpendicular to the large facets of the sample, whereas SSC is theoretically expected for B parallel to the surfaces. This feature has been already reported in Nb [14], NbSe 2 [23], MgB 2 [24] but the explanation is not straightforward.…”
Section: Resultsmentioning
confidence: 75%
“…However, under a low applied current, the electric resistance reaches its normal state value R n at much higher field, and hysteric magnetization is also observed up to B c3 ≈1.7 B c2 due to the existence of a finite critical current in the surface superconducting (SSC) state [17][18][19]. From V(I) curves (not shown here), we find that the differential resistance dV/d(I-I c )≈ R n as soon as B>B c2 as expected for a metallic bulk [14,20]. Then, from these different measurements, it is possible to identify both critical fields B c2 and B c3 at different temperatures.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation